Implementing Regional Inclusive Education Policies to Realize Education Without Borders: Implementasi Kebijakan Pendidikan Inklusif di Daerah untuk Mewujudkan Pendidikan Tanpa Batas - Azimatul Af'idah; Budi Purwoko; Mufarrihul Hazin (Universitas Muhammadiyah Sidoarjo, 2025)
Inclusive education serves as a cornerstone in promoting equitable learning opportunities for all, especially for Children with Special Needs (ABK). In Gresik Regency, the implementation of Regent Regulation No. 42/2013 reflects a local commitment to this ideal. However, despite formal policies, significant challenges persist. A lack of teacher training, inadequate infrastructure, and entrenched social stigma continue to obstruct meaningful inclusion. Existing studies have yet to comprehensively explore the interplay between these constraints and the policy’s intended outcomes, exposing a critical knowledge gap. This study aims to analyze the challenges and opportunities inherent in implementing inclusive education in Gresik and evaluate the effectiveness of support programs. Using a qualitative literature review approach, the findings reveal that while barriers are significant, notable opportunities exist through the empowerment of Special Guidance Teachers (GPK), enhanced training, strong policy backing, and multisectoral collaboration. The novelty lies in the synthesis of policy analysis with community and educational dynamics to propose an integrated strategic framework. The implications underscore the necessity of strengthening educator capacity, infrastructure, and social attitudes to achieve inclusive education goals—providing a foundation for developing future policies and localized best practices. Highlights: Highlights policy gaps and challenges in inclusive education. Emphasizes the role of Special Guidance Teachers (GPK). Proposes strategic collaboration for better policy outcomes. Keywords: Inclusive Education, Regional Policy, Special Needs Children, Educational Equity